2017
DOI: 10.1038/srep39526
|View full text |Cite
|
Sign up to set email alerts
|

Hampering Effect of Cholesterol on the Permeation of Reactive Oxygen Species through Phospholipids Bilayer: Possible Explanation for Plasma Cancer Selectivity

Abstract: In recent years, the ability of cold atmospheric pressure plasmas (CAPS) to selectively induce cell death in cancer cells has been widely established. This selectivity has been assigned to the reactive oxygen and nitrogen species (RONS) created in CAPs. To provide new insights in the search for an explanation for the observed selectivity, we calculate the transfer free energy of multiple ROS across membranes containing a varying amount of cholesterol. The cholesterol fraction is investigated as a selectivity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 75 publications
3
81
1
Order By: Relevance
“…Using model lipid‐like layers as found on cell membranes, non‐reactive MD simulations were carried out to study the sputtering process of these layers, induced by CAP‐generated Ar ion bombardment . Non‐reactive MD simulations were also applied to investigate the permeation of ROS through oxidized and non‐oxidized cell membranes, including the synergistic effect of plasma oxidation and electric field and the hampering effect of cholesterol . Finally, the effect of lipid oxidation on the phosphatidylserine translocation across the cell membrane, which plays a vital role in apoptosis signaling, was studied …”
Section: Introductionmentioning
confidence: 99%
“…Using model lipid‐like layers as found on cell membranes, non‐reactive MD simulations were carried out to study the sputtering process of these layers, induced by CAP‐generated Ar ion bombardment . Non‐reactive MD simulations were also applied to investigate the permeation of ROS through oxidized and non‐oxidized cell membranes, including the synergistic effect of plasma oxidation and electric field and the hampering effect of cholesterol . Finally, the effect of lipid oxidation on the phosphatidylserine translocation across the cell membrane, which plays a vital role in apoptosis signaling, was studied …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we studied the effect of lipid oxidation on phosphatidylserine translocation across the plasma membrane, which plays a vital role in apoptosis signaling [12]. Furthermore, we investigated the ROS oxidation of the head groups and lipid tails in the membrane [13], the permeation of ROS across oxidized and non-oxidized membranes, including the synergistic effect of plasma oxidation and electric field [14], and the hampering effect of cholesterol [15,16]. In general, our investigations showed that oxidation of the membrane leads to an increase in its fluidity and permeability to ROS, thereby affecting the abovementioned processes.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of studies have been done to identify the type and spatio-temporal distribution of ROS produced by biomedical plasmas and the reader is referred to [9,37] for details. Although the ROS composition between plasma devices may vary, it has been shown that plasma-derived ROS can oxidize lipids in the cell membrane, reduce the membrane fluidity and favour pore formation [38][39][40], a topic thoroughly reviewed in [19]. The permeabilization of the cell membrane facilitates the access of ROS into the intracellular compartment, as well as the release of cell contents to the ECM, as observed in necrotic cells [41].…”
Section: Plasma-derived Ros Cell Death and The Ecmmentioning
confidence: 99%